STUDY REGARDING THE USE OF HYPOCALORIC - HYPOLIPIDEMIC AND HYPOGLUCIDIC DIET AND PHYSICAL EXERCISE TO DECREASE BODY MASS IN ADULTS OVER 50 YEARS OLD - RADU I. ABABEI; CĂTĂLINA P. ABABEI; ADRIAN A. COTÎRLEȚ; MĂDĂLIN I. MIRON (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Today's society, with its fast pace and growing stress, leads to a complex motivation for the modern person's need for exercise. For the middle age adults (50-60 years old), the stimulation of their metabolism through physical effort has become a habit imposed also by changes in their lifestyle. This paper started from the hypothesis stating that the systematic practice of physical exercise under the form of fast pace walking, doubled by an adequate diet can contribute to one's weight loss and improve one's health, especially their blood pressure. This research represents a case study conducted on a over 50 years old male, former professional athlete. The experiment was based on two independent variables: nutritional and motor, with initial and final measurements. The final blood test results emphasize the beneficial role played by exercise and a balanced diet in regulating the human body. Basically, there was a shift from a pathological level to an almost normal state of health. The motor analysis shows that the optimal markers of energy consumption are, besides distance, the average pace and speed; thus, the authors are able to say that the exercise performed by the subject while fatigued did not have any effect on his body mass loss.